Vehicle event data recorder with transparent frame - YANG YONG (2017)
The utility model discloses a vehicle event data recorder with transparent frame includes the frame, and the frame material is transparent tempering plastics, and frame outline's front is parallel with frame outline's the back, and frame outline's the back is provided with prevents reflecting the device, be provided with the installing support on the frame side, the frame openly is provided with the lens, is provided with the display screen in the lens. The frame of transparent tempering plastics makes the frame of frame outside the lens be in transparency clarity, it amasss to have reduced this vehicle event data recorder's the every detail of sheltering from, this vehicle event data recorder's view blind zone has been reduced, be favorable to improving driving safety, and simultaneously, the installation position at the rear -view mirror is installed with the installing support to this driving, the lens is as the rear -view mirror, this vehicle event data recorder needn't set up all the other positions and